The last human : a guide to twenty-two species of extinct humans - Sarmiento, Esteban E.; Sawyer, G. J.; Milner, Richard, 1941-; Deak, Viktor; Johanson, Donald C.; Leakey, Meave G.; Tattersall, Ian. (New Haven [Conn.] : Yale University Press, 2007)
Full-color illustrations present three-dimensional reconstructions of what anthropologists and paleontologists believe to be early species of humans on the earth.
"A Peter N. Nv̈raumont book."
Includes bibliographical references (p. 251) and index.
Library Journal Starred, March 2007
Pub Weekly, December 2007
Booklist, February 2007
Choice, November 2007
Keywords: Fossil hominids; Human evolution; Evolution